Management of Infectious Processes of the Pleural Space: A Review - Ankur Girdhar; Adil Shujaat; Abubakr Bajwa (Pulmonary Medicine)
Pleural effusions can present in 40% of patients with pneumonia. Presence of an effusion can complicate the diagnosis as well as the management of infection in lungs and pleural space. There has been an increase in the morbidity and mortality associated with parapneumonic effusions and empyema. This calls for employment of advanced treatment modalities and development of a standardized protocol to manage pleural sepsis early. There has been an increased understanding about the indications and appropriate usage of procedural options at clinicians’ disposal.